Qualification of academic facilities for small-scale automated manufacture of autologous cell-based products. (November 2014) - Hourd, Paul; Chandra, Amit; Alvey, David; Ginty, Patrick; McCall, Mark; Ratcliffe, Elizabeth; Rayment, Erin; Williams, David J
Academic centers, hospitals and small companies, as typical development settings for UK regenerative medicine assets, are significant contributors to the development of autologous cell-based therapies. Often lacking the appropriate funding, quality assurance heritage or specialist regulatory expertise, qualifying aseptic cell processing facilities for GMP compliance is a significant challenge. The qualification of a new Cell Therapy Manufacturing Facility with automated processing capability, the first of its kind in a UK academic setting, provides a unique demonstrator for the qualification of small-scale, automated facilities for GMP-compliant manufacture of autologous cell-based products in these settings. This paper shares our experiences in qualifying the Cell Therapy Manufacturing Facility, focusing on our approach to streamlining the qualification effort, the challenges, project delays and inefficiencies we encountered, and the subsequent lessons learned.